2020
DOI: 10.1186/s12866-020-01723-9
|View full text |Cite
|
Sign up to set email alerts
|

Timing of complementary feeding is associated with gut microbiota diversity and composition and short chain fatty acid concentrations over the first year of life

Abstract: Background: Early introduction of complementary foods has been associated with various immune disorders, oxidative stress, and obesity in childhood. The gut microbiota and the short chain fatty acids (SCFAs) they produce are postulated to be on the causal pathway. The objective of this study was to determine if early complementary feeding (i.e. consumption of solids or non-water/formula liquids at or before 3 months) is prospectively associated with infant gut microbiota composition, diversity and SCFAs at 3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 69 publications
3
69
0
2
Order By: Relevance
“…For instance, exclusively breastfed infants had relatively more acetate in their stools as compared to non-breastfed infants (Bridgman et al, 2017), likely due to the fermentation of oligosaccharides present in human breast-milk by members of the Bifidobacterium genus (Azad et al, 2016). The introduction of solid food results in the establishment of different microbial colonizers, which change the SCFA profile in the fecal sample (Differding et al, 2020). However, direct and indirect effects of SCFA production in the early postnatal period on GBA and subsequent consequences for the development of the brain and behaviors are poorly understood.…”
Section: Short-chain Fatty Acidsmentioning
confidence: 99%
“…For instance, exclusively breastfed infants had relatively more acetate in their stools as compared to non-breastfed infants (Bridgman et al, 2017), likely due to the fermentation of oligosaccharides present in human breast-milk by members of the Bifidobacterium genus (Azad et al, 2016). The introduction of solid food results in the establishment of different microbial colonizers, which change the SCFA profile in the fecal sample (Differding et al, 2020). However, direct and indirect effects of SCFA production in the early postnatal period on GBA and subsequent consequences for the development of the brain and behaviors are poorly understood.…”
Section: Short-chain Fatty Acidsmentioning
confidence: 99%
“…After birth, according to the findings of Koenig et al [ 27 ], there were apparent chaotic shifts of microbiome from that endowed with genes facilitating lactate utilization and plant polysaccharide metabolism mediated by milk-based diet to increase in Bacteroidetes initiated by introduction of solid food that prepares the infant gut for adult diet. However, in the findings of Differding et al [ 28 ], the early introduction of infants to complementary food was associated with altered gut microbiota composition and butyric acid concentration, which have been previously identified as precursors to oxidative stress, immune disorder and obesity in childhood.…”
Section: Resultsmentioning
confidence: 99%
“…However, Bifidobacteria , together with Bacteroides , remain among the prevalent species found in children's microbiota even after the introduction of complementary feeding ( 146 ). A recent study showed that the early introduction (<3 months) of complementary food is associated with an altered microbial composition with a higher diversity and an accelerated maturation pattern ( 149 ). Increased fecal excretion of butyrate and other SCFAs is associated with both local and systemic effects.…”
Section: Early Nutrition As Modulator Of Microbiota In Relation To T1mentioning
confidence: 99%
“…Instead, the greater abundance of Akkermansia Muciniphila promotes an early growth of adult associated bacteria, impairing the growth of taxa typical of the developmental phase. Finally, the early introduction of food results in an increased concentration of fecal butyrate ( 149 ).…”
Section: Early Nutrition As Modulator Of Microbiota In Relation To T1mentioning
confidence: 99%